Simultaneous oxidation of trace organic contaminant and Mn(II) by Mn(VII): Accelerating role of dissolved oxygen. (December 2022) - Duan, Shule; Dong, Huiyu; Hou, Pin; Han, Gangsheng; Zhang, Bochao; Qiang, Zhimin
Abstract: Permanganate (Mn(VII)) is a widely used oxidant in water treatment, which can oxidize trace organic contaminants (TrOCs) and Mn(II). Interestingly, this study found that presence of Mn(II) could accelerate the abatement of bisphenol A by Mn(VII) only under oxic condition. Herein, the effects of Mn(II) and dissolved oxygen (DO) on the abatement of TrOCs by Mn(VII) oxidation and the related mechanism were investigated. Results indicate that DO was involved in the Mn(VII)/Mn(II) reaction, with the reaction stoichiometry of Δ[Mn(VII)]:Δ[Mn(II)] determined to be 1:2 and 1:1.5 in the presence and absence of DO, respectively. Quenching and electron paramagnetic resonance tests verified that both superoxide radicals (O2 − ) and reactive Mn species contributed to the accelerated abatement of TrOCs (bisphenol A, methyl phenyl sulfoxide, and methyl phenyl sulfone) in the Mn(VII)/Mn(II) process. Specifically, O2 − was produced through the one-electron reduction of DO and made an important contribution (32.4%–100%) to the abatement of selected TrOCs. This study reveals that Mn(II) could enhance TrOC abatement by Mn(VII) oxidation, and DO played a pivotal role in the Mn(VII)/Mn(II) process. Graphical abstract: Image 1 Highlights: Mn(II) could activate Mn(VII) for degrading TrOCs. Reaction stoichiometries of Δ[Mn(VII)]:Δ[Mn(II)] were 1:2 (w/O2 ) and 1:1.5 (w/o O2 ). DO was the precursor of O2 − in the reaction of Mn(VII) with Mn(II). O2 − made an important contribution (32.4–100%) to the abatement of TrOCs.